2018
DOI: 10.1038/s41598-018-27479-x
|View full text |Cite
|
Sign up to set email alerts
|

Damage-associated molecular pattern recognition is required for induction of retinal neuroprotective pathways in a sex-dependent manner

Abstract: Retinal degeneration is a common cause of irreversible blindness and is caused by the death of retinal light-sensitive neurons called photoreceptors. At the onset of degeneration, stressed photoreceptors cause retinal glial cells to secrete neuroprotective factors that slow the pace of degeneration. Leukemia inhibitory factor (LIF) is one such factor that is required for endogenous neuroprotection. Photoreceptors are known to release signals of cellular stress, called damage-associated molecular patterns (DAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…DAMPs have dual roles in the retina; e.g., fractalkine, which has been reported as a DAMP, is neuroprotective in rd10 retinas by signaling through its CX3CR1 receptor, preventing microglia-induced damage (Roche et al, 2016). Stressed photoreceptors release DAMPs early in degeneration to induce neuroprotective responses in retinal glial cells by interacting with receptors as Toll-like receptor 2, a DAMP receptor that increases in Müller glial cells during degeneration (Hooper et al, 2018). S1P promotes migration in Müller glial cells and RPE cells (Swaney et al, 2008; Simón et al, 2015), which might release it to the retina milieu to act as an autocrine signal and promote a fibrotic process and/or to act as a paracrine signal in photoreceptors, promoting neuroprotection.…”
Section: Sphingosine-1-phosphate a Formidable Double-edged Sword In mentioning
confidence: 99%
“…DAMPs have dual roles in the retina; e.g., fractalkine, which has been reported as a DAMP, is neuroprotective in rd10 retinas by signaling through its CX3CR1 receptor, preventing microglia-induced damage (Roche et al, 2016). Stressed photoreceptors release DAMPs early in degeneration to induce neuroprotective responses in retinal glial cells by interacting with receptors as Toll-like receptor 2, a DAMP receptor that increases in Müller glial cells during degeneration (Hooper et al, 2018). S1P promotes migration in Müller glial cells and RPE cells (Swaney et al, 2008; Simón et al, 2015), which might release it to the retina milieu to act as an autocrine signal and promote a fibrotic process and/or to act as a paracrine signal in photoreceptors, promoting neuroprotection.…”
Section: Sphingosine-1-phosphate a Formidable Double-edged Sword In mentioning
confidence: 99%
“…As TLR2 is mainly expressed by retinal microglial cells [ 18 , 19 ] and microglia are the primary reactive cells to retinal damage [ 20 , 21 ], we next investigated whether Tlr2 deletion affected the microglial response to RP. We used flow cytometry to analyze the retinal myeloid population in the rd10 model, in which we had previously characterized the temporal pattern of microglial activation [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial effects of targeting TLR2 have also been described in animal models of other neurodegenerative pathologies of the CNS, including Alzheimer’s and Parkinson’s diseases [ 35 , 36 ]. However, Hooper et al found that genetic deletion of Tlr2 worsened light-induced retinal damage in an albino mouse model [ 19 ]. While the reasons for the discrepancies between our findings and others, and those of the latter study are not clear, differences in the type of insult and the genetic background could contribute to the divergent outcomes, as well as the fact Hooper et al used non-pigmented mice.…”
Section: Discussionmentioning
confidence: 99%
“…PHR degeneration modulates the expression of Neurotrophin receptor genes in retinal MGC (Harada et al, 2000). PHRs have also been reported to release stress signals, the damage-associated molecular patterns (DAMPs) during degenerative processes of the retina, that orchestrate a broad neuroprotective response in MGC, including release of Leukemia Inhibitory Factor (LIF), a critical PHR survival factor (Hooper et al, 2018). A further putative signal might be glutamate, which PHRs release as a neurotransmitter; activation of NMDA receptors has been shown to increase proliferation and differentiation of hippocampal neural progenitor cells (Joo et al, 2007) and might have a similar effect on retinal MGC.…”
Section: Discussionmentioning
confidence: 99%